Genome‐wide association study with the risk of schizophrenia in a Korean population. Issue 2 (4th November 2015) - Kim, Lyoung Hyo; Park, Byung Lae; Cheong, Hyun Sub; Namgoong, Suhg; Kim, Ji On; Kim, Jeong‐Hyun; Shin, Joong‐Gon; Park, Chul Soo; Kim, Bong‐Jo; Kim, Jae Won; Choi, Ihn‐Geun; Hwang, Jaeuk; et al.
Abstract : Schizophrenia is regarded as a multifactorial and polygenic brain disorder that is attributed to different combinations of genetic and environmental risk factors. Recently, several genome‐wide association studies (GWASs) of schizophrenia have identified numerous risk factors, but the replication results remain controversial and ambiguous. To identify schizophrenia susceptibility loci in the Korean population, we performed a GWAS using the Illumina HumanOmni1‐Quad V1.0 Microarray. We genotyped 1, 140, 419 single nucleotide polymorphisms (SNPs) in 350 Korea schizophrenia patients and 700 control subjects, and approximately 620, 001 autosomal SNPs were passed our quality control. In the case–control analysis, the rs9607195 A>G on intergenic area 250 kb away from the ISX gene and the rs12738007 A>G on the intron of the MECR gene were the most strongly associated SNPs with the risk of schizophrenia ( P = 6.2 × 10 −8, OR = 0.50 and P = 3.7 × 10 −7, OR = 2.39, respectively). In subsequent fine‐mapping analysis, 6 SNPs of MECR were genotyped with 310 schizophrenia patients and 604 control subjects. The association of the MECR rs12738007, a top ranked‐SNP in GWAS, was replicated ( P = 1.5 × 10 −2, OR = 1.53 in fine mapping analysis, P = 1.5 × 10 −6, OR = 1.90 in combined analysis). The identification of putative schizophrenia susceptibility loci could provide new insights into genetic factors related with schizophrenia and clues for the development of diagnosis strategies. © 2015 Wiley Periodicals, Inc.